Formation Mechanism of Foamed Gel for Controlling the Coal Spontaneous Combustion. Issue 1 (2nd January 2016) - Zhang, Leilin; Qin, Botao; Shi, Biming; Wen, Kunpeng
ABSTRACT: In order to investigate the formation mechanism of foamed gel for preventing the spontaneous combustion of coal, the ZOOM645S stereomicroscope was adopted to explore the microstructures of foam with different components. It can be seen from the results that after thickener H and crosslinker AL are both added into the foam system, the microstructures of the foam system are regular and the films become thicker. According to atomic force microscopy and Fourier transform infrared spectroscopy, when thickener H is distributed into water, helical mesh polymer or double helix cluster will be formed among molecular chains; the active groups in the polymer or cluster fully contact and collide with those in the main chains of crosslinker AL, thus forming three-dimensional network structures. With the concentration of the blends mixed by thickener H and crosslinker AL increasing, the gelation time is shortened. If the concentration is 0.6%, the gelation effect is best. Further, the stability of foamed gel is also studied. The results show that, with the increase of temperature, the stability of foamed gel decreases, but the downward trend is obviously slower than that of common foam.